(untitled) (American Journal of Islam and Society, 1986)
I. political Allegiance: Nature and Extent The need for and the importance of government in Islam has been the subject of extensive research and debates since the early days of Islam. Naturally, there is a general consensus among Muslim jurists on the obligatory nature of installing a government or a kind of central authority to sakguad the very existence of the community. Although obedience to legitimate authority is qualified and conditional, the Shari’ah attaches great importance to fulfillment of the Muslims’ obligations trrward their legitimate government and considers it a religious obligation of the highest degree. As Muhammad Asad pointed out correctly, what is at stake here is the unity of the Community: So long as the state conforms in its principles and methods to the demands of the Shari’ah, a Muslim citizen’s duty of obedience to the govenment is a religious obligation. In the words of the prophet, "He who withdraws his hand from obedience [to the amir] will have nothing in his favor when he meets Allah on the Day of Resurrection; and he who dies without having considered himself bound by a pledge of allegiance [literally, ’While there is no pledge of allegiance on his neck’] had died the death of the Time of Ignorance [i.e., as an unbeliever]." In accordance with the principle of Muslim unity so strongly emphasized in the Qur’an and Sunnah, any attempt to disrupt that unity must be regarded in the Quran and Sunnah, any attempt to disrupt that unity must be regarded as a crime of the highest order-in fact, as high treason- and must be punished severely. Consequently, the Prophet commanded ...